Lithium titanate negative pole piece as well as preparation method and application thereof

By adding sulfide solid electrolytes, conductives and adhesives to the lithium -ion battery, build effective ions and electronic transmission channels to solve the problem of large changes in the volume of carbon materials during lithium -ion dehydration, and improve The cycle performance and magnification performance of the lithium -ion battery.

CN119340340APending Publication Date: 2025-01-21GTC-POWER ZHUHAI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411306329.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, carbon materials are used as negative electrode sheets. The volume changes greatly during the lithium-ion deintercalation process, which easily leads to failure of the lithium-ion cell. The electronic conductivity of lithium titanate is low and the conductivity is insufficient.

Method used

Using lithium titanate negative pole tablets, sulfide solid -state electrolytes, first electricals and first binders are added to the negative active substance layer to build a network -like ion transmission channel and electronic transmission channel to improve the cycle performance of the battery and Dialing performance.

Benefits of technology

It improves the cycle performance and rate performance of lithium-ion batteries, enhances the safety and conductivity of the battery, and avoids the formation and polarization of lithium dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340340A_ABST
    Figure CN119340340A_ABST
Patent Text Reader

Abstract

The invention provides a lithium titanate negative electrode plate and a preparation method and application thereof, the lithium titanate negative electrode plate comprises a negative electrode active material layer, the negative electrode active material layer comprises lithium titanate, sulfide solid electrolyte, a first conductive agent and a first binder, and the sulfide solid electrolyte accounts for 35-60 wt% of the total amount of the negative electrode active material layer. According to the lithium titanate negative electrode plate provided by the invention, an effective ion transmission channel and an effective electron transmission channel can be formed in the negative electrode active material layer at the same time, so that lithium ions and electrons can be effectively conducted, the lithium ions can be embedded or separated out in the cycle process, and the cycle performance and the rate capability of the battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium titanate negative electrode sheet and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic products such as mobile phones and laptops, as well as new energy vehicles, due to their high energy density, long cycle life, and environmental friendliness. In lithium-ion batteries, the negative electrode sheet, as a carrier of lithium ions, is often accompanied by a certain volume change during the cycle process. Carbon materials are used for negative electrodes, and the volume changes greatly during the lithium ion insertion and extraction process, which can easily lead to the failure of lithium-ion batteries. Therefore, based on the requirements for the safety and cycle performance of lithium-ion batteries, it is necessary to find new negative electrode materials to replace carbon materials.

[0003] Lithium titanate (Li 4 Ti 5 O 12 As a "zero strain" material, LTO has a crystal lattice constant and volume change of less than 1% during the process of lithium ion insertion or extraction, which can avoid structural damage caused by repeated expansion and contraction of electrode materials during charge and discharge cycles, thereby improving the cycle performance and service life of the electrode. Compared with carbon materials, lithium titanate has a high potential and a high lithium ion diffusion coefficient (2×10 -8 cm 2 / s), so that the negative electrode material can be charged and discharged quickly, and it is not easy to produce lithium dendrites, which has high safety. However, as a negative electrode material, lithium titanate has low electronic conductivity. Its own properties limit the conductivity of lithium titanate, and its rate performance under high current charging and discharging is poor.

[0004] In view of this, it is necessary to provide a new negative electrode plate to solve the above technical problems. Summary of the invention

[0005] The present invention aims to provide a negative electrode sheet having good conductivity, safety and cycle performance, and a preparation method and application thereof.

[0006] To solve the above problems, the first aspect of the present invention provides a lithium titanate negative electrode plate, including a negative electrode active material layer, wherein the negative electrode active material layer includes lithium titanate, a sulfide solid electrolyte, a first conductive agent and a first binder, and the content of the sulfide solid electrolyte accounts for 35wt% to 60wt% of the total amount of the negative electrode active material layer.

[0007] A second aspect of the present invention provides a method for preparing a lithium titanate negative electrode sheet, which is used to prepare the lithium titanate negative electrode sheet described in the above aspect, comprising the following steps:

[0008] The lithium titanate, the sulfide solid electrolyte, the first conductive agent and the first binder are mixed evenly to form a negative electrode active material layer by a dry method;

[0009] The negative electrode active material layer is pressed onto the surface of the negative electrode current collector to obtain a lithium titanate negative electrode sheet.

[0010] The third aspect of the present invention provides an all-solid-state soft-pack battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer, wherein the negative electrode sheet is the lithium titanate negative electrode sheet described in the first aspect, or is the lithium titanate negative electrode sheet prepared by the preparation method described in the second aspect.

[0011] The lithium titanate negative electrode plate described in the present invention uses lithium titanate as the negative electrode active material. Lithium titanate has a high potential and a high lithium ion diffusion coefficient, and lithium titanate is not easy to produce lithium dendrites. It has a high structural stability at high rates and high temperatures, which is beneficial to improving the safety of the battery. At the same time, a sulfide solid electrolyte and a first conductive agent are added to the negative electrode active material layer. The sulfide solid electrolyte has a high ion conductivity and can construct a network-like ion transmission channel in the negative electrode active material layer, which is convenient for rapid transmission of lithium ions. The first conductive agent has good electronic conductivity and can improve the electronic conductivity of the negative electrode active material layer, so that electrons are effectively conducted. A first binder is added to the negative electrode active material layer so that the lithium titanate, the sulfide solid electrolyte and the first conductive agent can be bonded to form a whole. The lithium titanate, the sulfide solid electrolyte and the first conductive agent are bonded to form a whole. The sulfide solid electrolyte and the first conductive agent work synergistically to simultaneously form effective ion transmission channels and electron transmission channels in the negative electrode active material layer, so that both lithium ions and electrons can be effectively conducted, which is beneficial to the embedding or extraction of lithium ions during the cycle process, and can effectively improve the cycle performance and rate performance of the battery; in addition, the content of the sulfide solid electrolyte accounts for 35wt% to 60wt% of the total amount of the negative electrode active material layer, which can not only avoid the inability of lithium ions to be effectively transmitted, causing the impedance of the positive electrode plate to be too large, resulting in poor battery cycle performance, but also the sulfide solid electrolyte can avoid the polarization phenomenon and interface side reactions caused by inconsistent lithium ion conductivity, and the sulfide solid electrolyte is relatively soft, which can increase the solid-solid contact between lithium titanate and the solid electrolyte layer and reduce its interface resistance.

[0012] The method for preparing the lithium titanate negative electrode sheet of the present invention prepares the negative electrode active material layer by dry method, and then presses the negative electrode active material layer to the surface of the negative electrode current collector to prepare the lithium titanate negative electrode sheet. No solvent is required in the entire preparation process, and the use of organic solvents can be completely avoided, which can not only save energy consumption, but also avoid the residual organic solvent affecting the production quality of the negative electrode sheet. The absence of solvent is also conducive to improving the safety and environmental protection of the preparation process. In addition, the production process of preparing the negative electrode active material layer by dry method is simple, has the advantage of amplification, can meet the requirements of industrialized production, and the preparation of thicker negative electrode sheets by dry method is conducive to controlling the thickness of the negative electrode sheets, and has great application potential.

[0013] The all-solid-state soft-pack battery described in the present invention, the positive electrode plate, the negative electrode plate and the solid electrolyte layer are all prepared by a dry method. The all-solid-state soft-pack battery does not contain an electrolyte, is less affected by the electrolyte, has higher safety, and can operate within a relatively wide temperature range, which is beneficial to expanding the application range of the battery; the solvent-free all-solid-state soft-pack battery is not only beneficial to controlling the thickness of the all-solid-state soft-pack battery, so that the thickness consistency between each battery is high, but also beneficial to reducing the internal resistance of the battery, thereby facilitating further improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A process flow chart for preparing a lithium titanate negative electrode sheet provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0015] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0016] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0017] In addition, the terms "comprising", "including", "containing", and "having" are not restrictive, that is, other steps and other components that do not affect the results can be added. Unless otherwise specified, materials, equipment, and reagents are commercially available.

[0018] In addition, although the present invention describes each step in the preparation process in the form of S110, S120, etc., this description is only for ease of understanding, and the form of S110, S120, etc. does not limit the sequence of the steps.

[0019] To solve the above technical problems, a first aspect of an embodiment of the present invention provides a lithium titanate negative electrode plate, which includes a negative electrode active material layer and a negative electrode current collector, wherein the negative electrode active material layer is arranged on at least one side surface of the negative electrode current collector, and the negative electrode active material layer includes lithium titanate, a sulfide solid electrolyte, a first conductive agent and a first binder, wherein the content of the sulfide solid electrolyte accounts for 35wt% to 60wt% of the total amount of the negative electrode active material layer.

[0020] The lithium titanate negative electrode plate provided in this embodiment uses lithium titanate as the negative electrode active material. Lithium titanate has a high potential and a high lithium ion diffusion coefficient. Lithium titanate is not easy to produce lithium dendrites. It has a high structural stability at high rates and high temperatures, which is beneficial to improving the safety of the battery. At the same time, a sulfide solid electrolyte and a first conductive agent are added to the negative electrode active material layer. The sulfide solid electrolyte has a high ion conductivity and can construct a network-like ion transmission channel in the negative electrode active material layer, which is convenient for rapid transmission of lithium ions. The first conductive agent has good electronic conductivity and can improve the electronic conductivity of the negative electrode active material layer, so that electrons can be effectively conducted. A first binder is added to the negative electrode active material layer so that the lithium titanate, the sulfide solid electrolyte and the first conductive agent can be bonded to form a whole. The lithium titanate, The sulfide solid electrolyte and the first conductive agent work synergistically to simultaneously form effective ion transmission channels and electron transmission channels in the negative electrode active material layer, so that both lithium ions and electrons can be effectively conducted, which is beneficial to the embedding or extraction of lithium ions during the cycle process, and can effectively improve the cycle performance and rate performance of the battery; in addition, the content of the sulfide solid electrolyte accounts for 35wt% to 60wt% of the total amount of the negative electrode active material layer, which can not only avoid the inability of lithium ions to be effectively transmitted, causing the impedance of the positive electrode plate to be too large, resulting in poor battery cycle performance, but also the sulfide solid electrolyte can avoid polarization phenomena and interfacial side reactions caused by inconsistent lithium ion conductivity, and the sulfide solid electrolyte is relatively soft, which can increase the solid-solid contact between lithium titanate and the solid electrolyte layer and reduce its interface resistance.

[0021] In this embodiment, the negative electrode active material layer includes 35wt% to 60wt% of lithium titanate, 35wt% to 60wt% of sulfide solid electrolyte, 1wt% to 10wt% of the first conductive agent, and 1wt% to 10wt% of the first binder. Therefore, controlling the amount of lithium titanate, sulfide solid electrolyte, first conductive agent, and first binder within the above range is conducive to maintaining the cycle performance and rate performance of the battery in a better state.

[0022] On the basis of the above embodiment, the content of lithium titanate is not less than the content of sulfide solid electrolyte. Therefore, when the content of lithium titanate is not less than the content of sulfide solid electrolyte, it is not only beneficial to reduce the formation of lithium dendrites and further improve the safety of the battery, but also beneficial to improve the cycle performance and rate performance of the battery.

[0023] Based on the above embodiment, the negative electrode active material layer includes 50wt% to 60wt% of lithium titanate, 36wt% to 46wt% of sulfide solid electrolyte, 1wt% to 5wt% of the first conductive agent and 1wt% to 5wt% of the first binder, which is conducive to further improving the cycle performance and rate performance of the battery.

[0024] Preferably, the negative electrode active material layer includes 50 wt % of lithium titanate, 46 wt % of sulfide solid electrolyte, 3 wt % of the first conductive agent and 1 wt % of the first binder.

[0025] In this embodiment, the sulfide solid electrolyte is Li 7 P 3 S 11 , Li 3 PS 4 , Li 6 PS 5 X and Li 11-x M 2-x P 1+x S 12 One or more combinations thereof, wherein X is any one of Cl, Br and I, and M is any one of Ge, Sn and Si. The specific value of x is not further limited in this embodiment, and can be determined by those skilled in the art according to actual conditions. Thus, the above-mentioned sulfide solid electrolyte has good stability, which is beneficial to improving the charge and discharge stability of the battery during the cycle process, and the above-mentioned sulfide solid electrolyte has good ionic conductivity, which is beneficial to improving the cycle performance and rate performance of the battery.

[0026] Based on the above embodiment, the sulfide solid electrolyte is Li 6 PS 5 Cl. Thus, Li 6 PS 5 Cl has high ionic conductivity and low activation energy at room temperature. It not only has good ionic conductivity at low temperatures, but also has high stability at high temperatures, which enables the battery to work stably in a wide temperature range and is beneficial to improving the battery's rate performance and cycle performance.

[0027] On the basis of the above embodiment, the particle size range of lithium titanate is 100nm to 500nm, and the particle size range of sulfide solid electrolyte is 1μm to 10μm. Preferably, the particle size range of lithium titanate is 200nm, and the particle size range of sulfide solid electrolyte is 3μm. Thus, the particle size of sulfide solid electrolyte is larger than that of lithium titanate, so that lithium titanate can be effectively filled between the particles of sulfide solid electrolyte, which is beneficial to improve the density of negative electrode active material layer, thereby improving the performance of battery.

[0028] In this embodiment, the first conductive agent is one or a combination of SuperP (SP), Ketjen black (KB), acetylene black (AB), conductive graphite, vapor grown carbon fiber (VGCF), carbon nanotube (CNT) and graphene. Preferably, the first conductive agent is vapor grown carbon fiber.

[0029] In this embodiment, the first binder is one or a combination of carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene butadiene rubber (SBR), linear three-block copolymer (SEBS) and polytetrafluoroethylene (PTFE). Preferably, the first binder is polytetrafluoroethylene.

[0030] In this embodiment, the negative electrode active material layer can be arranged on one side surface of the negative electrode current collector, and the negative electrode active material layer can also be arranged on both sides of the negative electrode current collector. The thickness of the single-sided negative electrode active material layer is 300μm to 400μm. Preferably, the thickness of the single-sided negative electrode active material layer is 300μm. Specifically, if the negative electrode active material layer is arranged on one side surface of the negative electrode current collector, the thickness of the negative electrode active material layer is 300μm to 400μm; if the negative electrode active material layer is arranged on both sides of the negative electrode current collector, the sum of the thickness of the negative electrode active material layer on both sides is 600μm to 800μm, and preferably, the thickness of the negative electrode active material layer on both sides is the same. Therefore, limiting the thickness of the negative electrode active material layer within the above range can avoid the negative electrode active material lithium titanate content being too low, so that the capacity of the battery cell is low and the decay is fast, and it can also avoid the overall thickness of the negative electrode active material layer, which affects the energy density of the battery.

[0031] Combination Figure 1 As shown, the second aspect of the embodiment of the present invention provides a method for preparing a lithium titanate negative electrode sheet, which is used to prepare the lithium titanate negative electrode sheet as in the first aspect, and the preparation method comprises the following steps:

[0032] Step S110: Evenly mix lithium titanate, sulfide solid electrolyte, a first conductive agent and a first binder, and prepare a negative electrode active material layer by a dry method.

[0033] Specifically, in this embodiment, lithium titanate, sulfide solid electrolyte and the first conductive agent can be mixed evenly to obtain a first mixture, and then the first mixture is mixed with the first binder to obtain a second mixture, and finally the second mixture is made into a negative electrode active material layer of a preset thickness. The mixing can include ball milling mixing or mechanical mixing.

[0034] In this embodiment, lithium titanate, sulfide solid electrolyte and the first conductive agent are first mixed so that the three are evenly mixed, which is beneficial to constructing ion transmission channels and electron transmission channels in the negative electrode active material layer. Then the first mixture is mixed with the first binder so that the first binder can be evenly dispersed in the first mixture, so that the lithium titanate, sulfide solid electrolyte and the first conductive agent can be bonded to form a whole.

[0035] Of course, in this embodiment, the lithium titanate, the sulfide solid electrolyte, the first conductive agent and the first binder may be uniformly mixed to obtain a mixture, and then the mixture may be made into a negative electrode active material layer of a preset thickness.

[0036] In this embodiment, a multi-roll mill can be used to form the negative electrode active material layer by dry rolling, and the negative electrode active material layer can be formed and extended by adjusting the differential speed between the rollers. In this embodiment, the speed ratio between the rollers and the spacing between the rollers during the dry rolling operation are not further limited, and those skilled in the art can set them according to actual conditions, as long as the negative electrode active material layer can be made into a preset thickness, wherein the preset thickness of the single-side negative electrode active material layer is 300μm to 400μm.

[0037] Step S120: Press the negative electrode active material layer onto the surface of the negative electrode current collector to obtain a lithium titanate negative electrode sheet.

[0038] Specifically, the negative electrode active material layer is pressed onto the surface of the negative electrode current collector by a preset pressure, and the negative electrode active material layer is bonded to the surface of the negative electrode current collector to obtain a lithium titanate negative electrode sheet. When the negative electrode active material layer is pressed onto the surface of the negative electrode current collector by a preset pressure, a temperature-raising auxiliary method can be used, that is, the negative electrode active material layer can be pressed onto the surface of the negative electrode current collector by a preset pressure at a preset temperature, thereby increasing the bonding force of the negative electrode active material layer onto the surface of the negative electrode current collector, and improving the structural strength and stability of the lithium titanate negative electrode sheet.

[0039] It should be noted that the preset pressure and the preset temperature are not further limited in this embodiment, and those skilled in the art may set them according to actual conditions.

[0040] The preparation method of the lithium titanate negative electrode sheet provided in this embodiment is to prepare the negative electrode active material layer by dry method, and then press the negative electrode active material layer to the surface of the negative electrode current collector to prepare the lithium titanate negative electrode sheet. No solvent is required in the entire preparation process, and the use of organic solvents can be completely avoided, which can not only save energy consumption, but also avoid the residual organic solvent affecting the production quality of the negative electrode sheet. The absence of solvent is also conducive to improving the safety and environmental protection of the preparation process. In addition, the production process of preparing the negative electrode active material layer by dry method is simple, and has the advantages of both amplification and can meet the requirements of industrialized production. In addition, the thicker negative electrode sheet prepared by dry method can match the positive electrode sheet with higher surface loading, which is conducive to improving the energy output of the battery and has great application potential.

[0041] The third aspect of an embodiment of the present invention provides an all-solid-state soft-pack battery, which includes a positive electrode plate, a negative electrode plate and a solid electrolyte layer, wherein the negative electrode plate is the lithium titanate negative electrode plate described in the first aspect, or is the lithium titanate negative electrode plate prepared by the preparation method described in the second aspect.

[0042] The positive electrode sheet of this embodiment includes a positive electrode active material layer and a positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, a sulfide solid electrolyte, a second conductive agent, and a second binder.

[0043] Specifically, the positive electrode active material layer includes 60wt% to 90wt% of positive electrode active material, 5wt% to 30wt% of sulfide solid electrolyte, 0.1wt% to 10wt% of second conductive agent and 0.1wt% to 10wt% of second binder. Thus, the amount of positive electrode active material, sulfide solid electrolyte, second conductive agent and second binder is controlled within the above range, which is matched with the negative electrode plate in this embodiment, which is conducive to improving the cycle performance and rate performance of the battery.

[0044] Preferably, the positive electrode active material layer includes 70 wt % of the positive electrode active material, 26.5 wt % of the sulfide solid electrolyte, 3 wt % of the second conductive agent and 0.5 wt % of the second binder.

[0045] In this embodiment, the positive electrode active material is lithium cobalt oxide (LiCoO 2 ), lithium nickel cobalt manganese oxide, lithium-rich layered oxides, spinel oxides and LiFePO 4 Thus, the selection of the above-mentioned positive electrode active materials can improve the capacity of the positive electrode active material layer, which is beneficial to improving the energy density of the battery.

[0046] Based on the above embodiment, the positive electrode active material is lithium nickel cobalt manganese oxide, whose general formula is LiNi x Co y Mnz O 2 , where x+y+z=1, x≥0.6. Therefore, lithium nickel cobalt manganese oxide has high gram capacity, good safety, low self-discharge rate, and good compatibility with a variety of electrolytes. Using it as a positive electrode active material is beneficial to improving the energy density and safety performance of the battery.

[0047] In this embodiment, the sulfide solid electrolyte in the positive electrode active material layer is Li 7 P 3 S 11 , Li 3 PS 4 , Li 6 PS 5 X and Li 11-x M 2-x P 1+x S 12 One or more of the combinations thereof, wherein X is any one of Cl, Br and I, and M is any one of Ge, Sn and Si. Therefore, the solid electrolyte in the positive electrode active material layer is also a sulfide solid electrolyte, which is the same type of solid electrolyte as that in the negative electrode active material layer, and can avoid polarization and interface side reaction caused by inconsistent ion conductivity, thereby increasing the internal resistance of the battery and improving the cycle performance of the battery.

[0048] Based on the above embodiment, the solid electrolyte in the positive electrode active material layer is Li 6 PS 5 Therefore, the use of the same sulfide solid electrolyte in the positive electrode active material layer as in the negative electrode active material layer is beneficial to further improve the electrochemical performance of the battery.

[0049] In this embodiment, the second conductive agent is one or a combination of SuperP (SP), Ketjen black (KB), acetylene black (AB), conductive graphite, vapor grown carbon fiber (VGCF), carbon nanotube (CNT) and graphene; the second binder is one or a combination of carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene butadiene rubber (SBR), linear three embedding copolymer (SEBS) and polytetrafluoroethylene (PTFE). Preferably, the second conductive agent is vapor grown carbon fiber, and the second binder is polytetrafluoroethylene. Therefore, the second conductive agent uses the same conductive agent as the first conductive agent, and the second binder uses the same binder as the first binder, which is conducive to the effective conduction of electrons in the battery.

[0050] In this embodiment, the positive electrode active material layer is made of the positive electrode active material, the sulfide solid electrolyte, the second conductive agent and the second binder by a dry method, and the positive electrode sheet is made by pressing the positive electrode active material layer to the surface of the positive electrode current collector. Specifically, the positive electrode active material, the sulfide solid electrolyte, the second conductive agent and the second binder are mixed evenly, and the positive electrode active material layer is prepared by a dry method, and the positive electrode active material layer is pressed to the surface of the positive electrode current collector to obtain the positive electrode sheet.

[0051] In this embodiment, the solid electrolyte layer includes 90wt% to 99.5wt% of a sulfide solid electrolyte and 0.5wt% to 10wt% of a third binder. Preferably, the solid electrolyte layer includes 99.5wt% of a sulfide solid electrolyte and 0.5wt% of a third binder. Therefore, the solid electrolyte layer provided in this embodiment uses a sulfide solid electrolyte, which can avoid polarization phenomena and interface side reactions caused by inconsistent ionic conductivity, and sulfide solid electrolytes are selected in the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer, which is beneficial to improve the bonding at the interface, weaken the interface impedance, and help reduce the internal resistance of the battery, thereby further improving the cycle performance of the battery.

[0052] The third binder is one or a combination of carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene butadiene rubber (SBR), linear three-block copolymer (SEBS) and polytetrafluoroethylene (PTFE). Preferably, the third binder is polytetrafluoroethylene.

[0053] In this embodiment, the solid electrolyte layer is prepared by a dry process using a sulfide solid electrolyte and a third binder. Specifically, the sulfide solid electrolyte and the third binder are mixed evenly and prepared into a solid electrolyte layer by a dry process.

[0054] In this embodiment, the all-solid-state soft-pack battery is prepared by the following preparation method:

[0055] Step S210, stacking the positive electrode sheet, the solid electrolyte layer and the lithium titanate negative electrode sheet in sequence to obtain a battery cell;

[0056] Step S220, encapsulating the battery cell into a shell, and after the encapsulation is completed, a packaged battery cell is obtained;

[0057] Step S230: Press the packaged battery cells to obtain an all-solid-state soft-pack battery.

[0058] In the all-solid-state soft-pack battery provided in the present embodiment, the positive electrode plate, the negative electrode plate and the solid electrolyte layer are all prepared by a dry method. The all-solid-state soft-pack battery does not contain an electrolyte, is less affected by the electrolyte, has higher safety, and can operate within a relatively wide temperature range, which is beneficial to expanding the scope of application of the battery. In addition, in the present embodiment, after the battery cell is prepared by lamination, it is pressed to obtain an all-solid-state soft-pack battery, which is not only beneficial to controlling the thickness of the battery and making the thickness consistency between each battery high, but also beneficial to reducing the internal resistance of the battery, thereby facilitating further improving the cycle performance of the battery.

[0059] In order to further explain the present invention in detail, the present invention will be further explained in conjunction with specific examples. The experimental methods used in the examples of the present invention are conventional methods unless otherwise specified; the materials, reagents, etc. used in the examples of the present invention are purchased from the market unless otherwise specified.

[0060] Example 1

[0061] This embodiment provides a lithium titanate negative electrode plate, which is prepared by the following method:

[0062] (1) Prepare the materials according to the following mass percentages: 50 wt% lithium titanate, 45 wt% sulfide solid electrolyte Li 6 PS 5 Cl, 4wt% vapor-grown carbon fiber and 1wt% polytetrafluoroethylene, lithium titanate, sulfide solid electrolyte Li 6 PS 5 Cl and vapor-grown carbon fiber are mixed evenly to obtain a first mixture, and the first mixture is then mixed with polytetrafluoroethylene to obtain a second mixture, and finally the second mixture is made into a negative electrode active material layer, and the thickness of the negative electrode active material layer is 300 μm.

[0063] (2) Pressing the negative electrode active material layer onto the surface of the negative electrode current collector to obtain a lithium titanate negative electrode sheet.

[0064] Example 2

[0065] This embodiment provides a lithium titanate negative electrode plate, which is prepared by the following method:

[0066] (1) Prepare the materials according to the following mass percentages: 50 wt% lithium titanate, 41 wt% sulfide solid electrolyte Li 6 PS 5 Cl, 4wt% vapor-grown carbon fiber and 5wt% polytetrafluoroethylene, lithium titanate, sulfide solid electrolyte Li 6 PS 5Cl and vapor-grown carbon fiber are mixed evenly to obtain a first mixture, and the first mixture is then mixed with polytetrafluoroethylene to obtain a second mixture, and finally the second mixture is made into a negative electrode active material layer, and the thickness of the negative electrode active material layer is 300 μm.

[0067] (2) Pressing the negative electrode active material layer onto the surface of the negative electrode current collector to obtain a lithium titanate negative electrode sheet.

[0068] Example 3

[0069] This embodiment provides a lithium titanate negative electrode plate, which is prepared by the following method:

[0070] (1) Prepare the materials according to the following mass percentages: 60 wt% lithium titanate, 35 wt% sulfide solid electrolyte Li 6 PS 5 Cl, 4wt% vapor-grown carbon fiber and 1wt% polytetrafluoroethylene, lithium titanate, sulfide solid electrolyte Li 6 PS 5 Cl and vapor-grown carbon fiber are mixed evenly to obtain a first mixture, and the first mixture is then mixed with polytetrafluoroethylene to obtain a second mixture, and finally the second mixture is made into a negative electrode active material layer, and the thickness of the negative electrode active material layer is 300 μm.

[0071] (2) Pressing the negative electrode active material layer onto the surface of the negative electrode current collector to obtain a lithium titanate negative electrode sheet.

[0072] Example 4

[0073] This embodiment provides a lithium titanate negative electrode plate, and the preparation method of the lithium titanate negative electrode plate is the same as the preparation method in Example 1, except that the thickness of the negative electrode active material layer in this embodiment is 400 μm.

[0074] Comparative Example 1

[0075] In this comparative example, a lithium titanate negative electrode sheet is provided. The preparation method of the lithium titanate negative electrode sheet is the same as the preparation method in Example 1, except that the materials are prepared according to the following mass percentages: 50wt% lithium titanate, 47wt% sulfide solid electrolyte Li 6 PS 5 Cl and 3wt% vapor grown carbon fibers.

[0076] Comparative Example 2

[0077] In this comparative example, a lithium titanate negative electrode sheet is provided. The preparation method of the lithium titanate negative electrode sheet is the same as the preparation method in Example 1, except that the materials are prepared according to the following mass percentages: 35wt% lithium titanate, 60wt% sulfide solid electrolyte Li6 PS 5 Cl, 4wt% vapor grown carbon fiber and 1wt% polytetrafluoroethylene.

[0078] Comparative Example 3

[0079] This embodiment provides a lithium titanate negative electrode plate. The preparation method of the lithium titanate negative electrode plate is the same as the preparation method in Example 1, except that the thickness of the negative electrode active material layer in this embodiment is 150 μm.

[0080] An all-solid-state soft-pack battery was prepared according to the following method to test the effect of each lithium titanate negative electrode sheet on the battery performance, wherein the negative electrode sheet used the lithium titanate negative electrode sheet prepared in Example 1 to Example 4 and the lithium titanate negative electrode sheet prepared in Comparative Example 1 to Comparative Example 3 respectively:

[0081] (1) Preparation of positive electrode sheet: Prepare the materials according to the following mass percentages: 70wt% lithium nickel cobalt manganese oxide, 26.5wt% sulfide solid electrolyte Li 6 PS 5 Cl, 3wt% vapor-grown carbon fiber and 0.5wt% polytetrafluoroethylene, lithium nickel cobalt manganese oxide, sulfide solid electrolyte Li 6 PS 5 Cl, vapor-grown carbon fiber and polytetrafluoroethylene are uniformly mixed, and a positive electrode active material layer is prepared by a dry method. The positive electrode active material layer is pressed onto the surface of a positive electrode current collector to obtain a positive electrode sheet.

[0082] (2) Solid electrolyte layer: 99.5wt% sulfide solid electrolyte Li 6 PS 5 Cl and 0.5 wt% of polytetrafluoroethylene are uniformly mixed and prepared into a solid electrolyte layer by a dry method.

[0083] (3) The positive electrode sheet, the solid electrolyte layer and the lithium titanate negative electrode sheet are stacked in sequence to obtain a stacked battery cell, and the battery cell is packaged in a shell. After the packaging is completed, the packaged battery cell is pressed to obtain an all-solid-state soft-pack battery.

[0084] The performance of the all-solid-state soft-pack batteries prepared using the lithium titanate negative electrode sheets of Examples 1 to 4 and Comparative Examples 1 to 3 was tested:

[0085] First coulombic efficiency: The first cycle uses a 0.1C rate to charge and discharge. The ratio of the first cycle discharge capacity to the charge capacity is the first coulombic efficiency.

[0086] First discharge specific capacity: The first cycle uses a 0.1C rate for charge and discharge. The ratio of the first cycle discharge capacity to the mass of the active material is the first discharge specific capacity.

[0087] Cycle performance: Capacity retention after 100 cycles of charge and discharge at 1C rate.

[0088] The performance test results of each embodiment and comparative example are shown in Table 1.

[0089] Table 1

[0090] Group First coulombic efficiency (%) First discharge specific capacity (mAh / g) Cycle performance (%) Example 1 82.23 172.27 93.13 Example 2 80.62 163.68 89.26 Example 3 81.54 168.92 90.25 Example 4 83.24 175.60 90.25 Comparative Example 1 -- -- -- Comparative Example 2 70.37 147.42 73.26 Comparative Example 3 56.48 120.30 72.16

[0091] It can be seen from Examples 1 to 4 and Comparative Example 2 in Table 1 that when the content of lithium titanate is lower than that of the sulfide solid electrolyte, the first coulombic efficiency, the first discharge specific capacity and the cycle performance of the all-solid-state soft-pack battery are inferior to those of the negative electrode sheet with a lithium titanate content higher than that of the sulfide solid electrolyte. This shows that the content of lithium titanate added to the negative electrode sheet is higher than that of the sulfide solid electrolyte, which is beneficial to improving the performance of the all-solid-state soft-pack battery; It can be seen from Examples 1 to 4 and Comparative Example 1 that if no binder is added to the negative electrode sheet, the negative electrode sheet cannot be formed, and it cannot be assembled into an all-solid-state soft-pack battery later, which shows that the binder is the negative electrode sheet in this embodiment. One of the indispensable components in the battery; it can be seen from Example 1, Example 4 and Comparative Example 3 that if the negative electrode sheet is thinner, the content of lithium titanate is less, so that the amount of lithium ions accommodated in the negative electrode sheet is limited, thereby reducing the content of reversible circulating lithium of the all-solid-state soft-pack battery, and the capacity of the all-solid-state soft-pack battery is lower and decays faster. If the negative electrode sheet is thicker, the content of lithium titanate is higher. During charging, the lithium ions released from the positive electrode sheet can be completely embedded in the lithium titanate of the negative electrode sheet, so that the potential of the positive electrode sheet becomes higher, so that the structure of the positive electrode sheet is very likely to be destroyed during the cycle, thereby affecting the cycle performance. Therefore, the optimal thickness of the negative electrode sheet is 300μm. It can be seen from the examples and example 2 that when the content of the binder is high, it will affect the ionic conductivity and electronic conductivity of the negative electrode sheet, thereby affecting the transmission of lithium ions and electrons inside the negative electrode sheet and the capacity retention rate of the all-solid-state soft-pack battery. Therefore, in this embodiment, the mass percentage of the binder is controlled to be 1wt% to 10wt%, and the optimal mass percentage of the binder is 1wt%. It can be seen from examples 1 and 3 that when the contents of lithium titanate and sulfide solid electrolyte are relatively close, it is beneficial to improve the electrical performance of the all-solid-state soft-pack battery. In the present invention, when the negative electrode active material layer includes 50wt% of lithium titanate, 45wt% of sulfide solid electrolyte, 4wt% of the first conductive agent and 1wt% of the first binder, the electrical performance of the all-solid-state soft-pack battery is the best.

[0092] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A lithium titanate negative electrode plate, characterized in that: The invention comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises lithium titanate, a sulfide solid electrolyte, a first conductive agent and a first binder, and the content of the sulfide solid electrolyte accounts for 35wt% to 60wt% of the total amount of the negative electrode active material layer.

2. The lithium titanate negative electrode sheet according to claim 1, characterized in that: The negative active material layer includes 35 wt % to 60 wt % of lithium titanate, 35 wt % to 60 wt % of a sulfide solid electrolyte, 1 wt % to 10 wt % of a first conductive agent, and 1 wt % to 10 wt % of a first binder.

3. The lithium titanate negative electrode sheet according to claim 2, characterized in that: The content of the lithium titanate is not less than the content of the sulfide solid electrolyte.

4. The lithium titanate negative electrode sheet according to claim 3, characterized in that: The negative active material layer includes 50 wt % to 60 wt % of lithium titanate, 36 wt % to 46 wt % of a sulfide solid electrolyte, 1 wt % to 5 wt % of a first conductive agent, and 1 wt % to 5 wt % of a first binder.

5. The lithium titanate negative electrode sheet according to claim 1, characterized in that: The sulfide solid electrolyte is Li7P3S 11 , Li3PS4, Li6PS5X and Li 11-x M 2-x P 1+x S 12 One or a combination of the foregoing, wherein X is any one of Cl, Br and I, and M is any one of Ge, Sn and Si.

6. The lithium titanate negative electrode sheet according to claim 1, characterized in that: The invention also comprises a negative electrode current collector, wherein the negative electrode active material layer is arranged on at least one side surface of the negative electrode current collector, and the thickness of the negative electrode active material layer is 300 μm to 400 μm.

7. A method for preparing a lithium titanate negative electrode sheet, characterized in that: The method for preparing the lithium titanate negative electrode sheet according to any one of claims 1 to 6 comprises the following steps: The lithium titanate, the sulfide solid electrolyte, the first conductive agent and the first binder are mixed evenly to form a negative electrode active material layer by a dry method; The negative electrode active material layer is pressed onto the surface of the negative electrode current collector to obtain a lithium titanate negative electrode sheet.

8. An all-solid-state soft-pack battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer, wherein the negative electrode sheet is the lithium titanate negative electrode sheet as claimed in any one of claims 1 to 6, or is the lithium titanate negative electrode sheet prepared by the preparation method as claimed in claim 7.

9. The all-solid-state soft-pack battery according to claim 8, characterized in that: The positive electrode plate comprises a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer is prepared by a dry method from a positive electrode active material, a sulfide solid electrolyte, a second conductive agent and a second binder. The positive electrode plate is prepared by pressing the positive electrode active material layer onto the surface of the positive electrode current collector.

10. The all-solid-state soft-pack battery according to claim 9, characterized in that: The solid electrolyte layer includes a sulfide solid electrolyte.